Optimisasi Pengembangan Aplikasi Koperasi Tenaga Kerja Bongkar Muat Pelabuhan Laut Nabire Berbasis Web Dengan Pendekatan Metode Spiral - Prayitno, Gunawan; Womsiwor, Marselina (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Manual management of cooperatives at Nabire Sea Port creates various obstacles, such as recording errors, time inefficiencies, and lack of transparency in financial management and distribution of loading and unloading tasks. This research aims to optimize the development of web-based loading and unloading labor cooperative applications using the spiral development method. The spiral method was chosen because its approach is iterative and allows for continuous improvement based on user feedback at each stage of development. The research results show that this application has succeeded in increasing the operational efficiency of cooperatives in terms of managing membership, savings, loans and task distribution. This web-based application also provides more transparent and real-time data access, which facilitates the decision-making process by cooperative administrators. Another advantage of the spiral method is its ability to identify and reduce the risk of system failure early, although this method requires more time and resources than other development methods. The development of a cooperative application using a spiral approach provides an effective digital solution in managing the Stevedoring and Unloading Workers' cooperative at Nabire Sea Port. However, challenges in the form of limited technological infrastructure and user training need to be overcome to achieve more optimal results in the future